2017
DOI: 10.2147/dddt.s135711
|View full text |Cite
|
Sign up to set email alerts
|

Antiglioma effects of cytarabine on leptomeningeal metastasis of high-grade glioma by targeting the PI3K/Akt/mTOR pathway

Abstract: Leptomeningeal metastasis (LM) of high-grade glioma is a highly lethal disease requiring new effective therapeutic measures. For both de novo or relapsed glioma with LM, intrathecal cytarabine chemotherapy is not frequently used for first-line and relapse protocols. We encountered a clinical case demonstrating effective application of cytarabine in high-grade glioma with LM, prompting us to explore the effects of cytarabine on malignant glioma and molecular mechanisms of such effects through in vivo and in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Following phosphorylation by PI3K, AKT acts on the downstream target proteins caspase-9, Bad, glycogen synthase kinase-3β, and eNOS. AKT is also involved in cell proliferation and apoptosis ( Yoon, 2017 ; Zhao et al, 2017 ). Nitric oxide (NO) is not only an endogenous anti-atherosclerotic factor, but also an important indicator of endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Following phosphorylation by PI3K, AKT acts on the downstream target proteins caspase-9, Bad, glycogen synthase kinase-3β, and eNOS. AKT is also involved in cell proliferation and apoptosis ( Yoon, 2017 ; Zhao et al, 2017 ). Nitric oxide (NO) is not only an endogenous anti-atherosclerotic factor, but also an important indicator of endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that the activation of the Akt/mTOR pathway induced by the long noncoding RNAs OECC [ 23 ] and MetaLnc9 [ 24 ] and the transmembrane 7 superfamily member 4 [ 25 ] promotes metastatic progression; conversely, the suppression of the Akt/mTOR pathway in the presence of the ferulic acid derivative FXS-3 [ 26 ], cardamonin [ 27 ] and microRNA-520a-3p [ 28 ] inhibits the metastatic potential of lung cancer cells. Accordingly, the association of the Akt/mTOR pathway with metastatic progression has been reported in other cancer types, including colorectal cancer [ 29 – 31 ], hepatocellular carcinoma [ 32 – 34 ], endometrial cancer [ 35 , 36 ], ovarian cancer [ 37 ], gastric cancer [ 38 – 40 ], melanoma [ 41 ], glioma [ 42 , 43 ], pancreatic ductal adenocarcinoma [ 44 ], nasopharyngeal carcinoma [ 45 , 46 ], osteosarcoma [ 47 – 50 ], renal cell carcinoma [ 51 53 ] and prostate cancer [ 54 56 ]. In breast cancer, synaptopodin-2 [ 57 ] and caveolin-1 [ 58 ] have been shown to modulate Akt/mTOR-regulated metastatic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of HIF-1α in glioma cells reduces migration and impairs their ability to form tumour spheres 35 . Recently, evidence suggested that cytarabine attenuates the leptomeningeal metastasis of high-grade glioma by targeting the PI3K/Akt/ mTOR pathway 36 . The Hippo signalling pathway is considered a key player in the regulation of tumourigenesis, and inactivating the Hippo signalling pathway enhances stem cell-like phenotypes in glioblastoma 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%